Assessment of the effectiveness of freight transportation by one-type transport vehicles - Галкін, Андрій Сергійович (Technology audit and production reserves, 2013)
Types of transport vehicles and the need for them are set on the basis of the study of in-plant freight traffic that is the volume of freight, transported for a certain period of time in a certain direction between the points of loading and unloading. Unstable freight flows, which change every day, are typical for most enterprises, so the need for transport vehicles is determined on the basis of their irregularity. In such conditions, it does not matter to customers how effectively transport vehicles or vehicle fleet as a whole will be used. On the other hand, from the point of view of a carrier, efficient use of vehicles is based on the organization and planning of the use of transport vehicles. Modern economic relations form a new approach to the formation of efficiency indicators, which is aimed at receiving profit in the long-term prospect. Therefore, the problem of assessing the effectiveness of freight transportation by transport vehicles is relevant for consideration. The method for assessing the efficiency of freight transportation by one-type transport vehicles with the ability of hiring and use of the project approach using modeling, graphic-analytical, economic-mathematical methods was improved. The methods of distribution of freight, suitable for transportation by the one-type transport vehicles, between the own and hired transport vehicles in conditions of ensuring the fulfillment of treaty obligations to the customer gained further development. Indicators of transportation efficiency assessment were analyzed.